Boron delivery agents for neutron capture therapy of cancer. Issue 1 (19th June 2018) - Barth, Rolf F.; Mi, Peng; Yang, Weilian
Abstract: Boron neutron capture therapy (BNCT) is a binary radiotherapeutic modality based on the nuclear capture and fission reactions that occur when the stable isotope, boron‐10, is irradiated with neutrons to produce high energy alpha particles. This review will focus on tumor‐targeting boron delivery agents that are an essential component of this binary system. Two low molecular weight boron‐containing drugs currently are being used clinically, boronophenylalanine (BPA) and sodium borocaptate (BSH). Although they are far from being ideal, their therapeutic efficacy has been demonstrated in patients with high grade gliomas, recurrent tumors of the head and neck region, and a much smaller number with cutaneous and extra‐cutaneous melanomas. Because of their limitations, great effort has been expended over the past 40 years to develop new boron delivery agents that have more favorable biodistribution and uptake for clinical use. These include boron‐containing porphyrins, amino acids, polyamines, nucleosides, peptides, monoclonal antibodies, liposomes, nanoparticles of various types, boron cluster compounds and co‐polymers. Currently, however, none of these have reached the stage where there is enough convincing data to warrant clinical biodistribution studies. Therefore, at present the best way to further improve the clinical efficacy of BNCT would be to optimize the dosing paradigms and delivery of BPA and BSH, either alone or in combination, with the hope that future research will identify new and better boron delivery agents for clinical use.